Marquis de la Vega Inclan and others studying model of eastern side of Court of the Universe - Cardinell-Vincent:::::::::
Marquis de la Vega Inclan was a special representative of the Spanish Government. Studying model at New Zealand Building, 334 California Street, San Francisco, California.